Peran Tim Pencegahan dan Penanganan Kekerasan (Tppk) dalam Implementasi Sekolah Ramah Anak (SRA) Jenjang PAUD Se-Kecamatan Tandes Kota Surabaya - Setiyono, Agus; Imron Arifin; Pramono; Eny Nur Aisyah; Prastyo, Danang; Iftitah, Selfi Lailiyatul (Institut Agama Islam Negeri Madura, 2024)
This research aims to determine the role of the TPPK (Violence Prevention and Control Team) SRA (Child-Friendly School) in the implementation of early childhood education at the PAUD unit level in Tandes District, Surabaya City. This research is descriptive qualitative. The data obtained in this work was carried out with the help of a literature review and field research, using several data collection methods, namely. observation, interviews, and documentation. Data analysis was carried out descriptively to determine the role of TPPK in the child-friendly school model at the PAUD level in Surabaya City, Tandes District. The results of the data analysis show that the role of TPPK in the child-friendly school model for early childhood in Tandes District, Surabaya City is quite good. In practice, the role of TPPK residents in educational activities according to the principles of Child-Friendly Schools is almost close to the existing theory. This is proven by the results of observations and documents carried out at all levels of PAUD units in Tandes District, Surabaya. The researcher's observations and documentation focused on the completeness of TPPK data, action programs and facilities and infrastructure used in early childhood education units, implementation of teaching methods, attitudes towards students and environmental health in early childhood education units in Tandes sub-district, Surabaya city which are organized in this way in such a way that the environment generally supports children's physical, spiritual and motoric activities. The application of learning methods designed and prepared by TPPK alone, especially teachers as learning leaders, cannot be implemented optimally for several reasons. Apart from that, teachers are quite varied in using teaching methods that are adapted to the material and supported by a game environment in delivering educational material, as well as active communication between teachers and students.